Preparation and in vitro characterization of the transdermal drug delivery system containing tamoxifen citrate for breast cancer - Adhyapak, Anjana; BG, Desai (Asian Journal of Pharmaceutics (AJP), 2014)
A matrix-type transdermal drug delivery system of tamoxifen citrate was developed by using a different ratio of eudragit- RL100, hydroxypropyl methyl cellulose (HPMC-K15), and ethyl cellulose (EC), by the solvent evaporation technique.The effect of the binary mixture of polymers with a penetration enhancer on the physical chemical parameters including, thickness, folding endurance, uniformity of drug content, moisture content, moisture uptake, tensile strength, and in vitro drug permeation were evaluated. The in vitro drug permeation studies were conducted by using modified Keshary-Chein diffusion cells through female Sprague Dawley rat skin using pH 7.4 phosphate buffer saline (PBS).The selected formulation’s stability studies were conducted as per the International Conference on Harmonization (ICH) guidelines, and did not show any degradation of the drug.